ANALISIS PEMASARAN KEMIRI RAKYAT DI DESA PERBULAN, KECAMATAN LAUBALENG, KABUPATEN KARO (Marketing Analysis of Private Candlenut in Perbulan Village, Laubaleng Subdistrict, Karo District) - Silvi Yulia Br Singarimbun; Agus Purwoko; Oding affandi (Peronema Forestry Science Journal, 2013)
Candlenut is the non-timber forest product, that seeds are used as an oil source and spices. This study aims to determine the candlenut marketing channels, marketing margin and marketing efficiency levels candlenut Perbulan Village, Laubaleng Subdistrict, Karo District. The method used in this research was purposive sampling and snowball sampling method to determine the flow of marketing. The results showed that there are four candlenut marketing channels. The average marketing margin earned by farmers is 69,75%, the traders paring receives an average marketing margin 17,21%, traders village receives an average marketing margin 1,90%, average marketing margin earned by district collector is 5,16% and the dealer receive marketing margin 5,43%. Candlenut marketing that took place in the Perbulan village generally efficient. The most efficient marketing channel is a marketing channel II with the marketing efficiency of  2,34%. Keywords: marketing efficiency, candlenut, marketing chain, marketing margin